2020
DOI: 10.1016/j.jrp.2020.104035
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of linguistic markers of extraversion: Positive emotion and social process words

Abstract: Past literature has shown that extraversion is related to the use of positive emotion and social process words. However, the strength of the relationships varies substantially across studies. In this research, we conducted a meta-analysis (k = 37, N = 82,132) to estimate the overall effect size of the two linguistic correlates of extraversion. In addition, we tested potential moderators including demographic variables (e.g., age and gender) and communication contexts (e.g., synchronous vs. asynchronous, public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 100 publications
(121 reference statements)
2
23
2
Order By: Relevance
“…The large number of existing studies speaks to the high relevance of this research, both in terms of establishing consensus between studies and in revealing relationships with other variables as support for concurrent validity with the results of established measures. However, recent studies have also raised important questions about the generalizability of existing findings beyond the original context of investigation, which has highlighted potential constraints on their validity in different languages and cultures (Garimella et al, 2016;Basnight-Brown and Altarriba, 2018;Jackson et al, 2019;Sánchez-Rada and Iglesias, 2019;Chen et al, 2020;Thompson et al, 2020;Dudãu and Sava, 2021). The results of the studies also indicate that the comparison and psychological interpretation of linguistic phenomena between different cultures and languages is subject to several fundamental challenges.…”
Section: Challenges In Cross-language Psychological Text Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The large number of existing studies speaks to the high relevance of this research, both in terms of establishing consensus between studies and in revealing relationships with other variables as support for concurrent validity with the results of established measures. However, recent studies have also raised important questions about the generalizability of existing findings beyond the original context of investigation, which has highlighted potential constraints on their validity in different languages and cultures (Garimella et al, 2016;Basnight-Brown and Altarriba, 2018;Jackson et al, 2019;Sánchez-Rada and Iglesias, 2019;Chen et al, 2020;Thompson et al, 2020;Dudãu and Sava, 2021). The results of the studies also indicate that the comparison and psychological interpretation of linguistic phenomena between different cultures and languages is subject to several fundamental challenges.…”
Section: Challenges In Cross-language Psychological Text Analysismentioning
confidence: 99%
“…At the time of writing this article, 781 records were available on the Web of Science that contained "LIWC" or "Linguistic Inquiry and Word Count" as the topic, and more than twenty thousand records are listed on Google Scholar. In its current version, LIWC2015, the program offers an intuitive user interface and provides a simple and clear output of the results (Pennebaker et al, 2015), including a range of comparison possibilities (Chen et al, 2020). LIWC dictionaries have been translated and adapted into multiple languages, including Spanish (Ramírez-Esparza et al, 2007), French (Piolat et al, 2011), German (Wolf et al, 2008;Meier et al, 2019), Dutch (Boot et al, 2017;Van Wissen and Boot, 2017), Brazilian-Portuguese (Balage Filho et al, 2013;Carvalho et al, 2019), Chinese (Huang et al, 2012), Serbian (Bjekić et al, 2014), Italian (Agosti and Rellini, 2007), Russian (Kailer and Chung, 2007), Arabic (Hayeri, 2014), Japanese (Shibata et al, 2016), and Romanian (Dudãu and Sava, 2020).…”
Section: The Linguistic Inquiry and Word Count Program As An Examplementioning
confidence: 99%
See 1 more Smart Citation
“…The affect-as-information model suggests that people use affect as a heuristic and substitute it for objective criteria when making social judgments (Barsky and Kaplan, 2007). It has been found that extraversion is positively related to general happiness and positive affect (Chen et al, 2020). Individuals who need to make judgments under circumstances of uncertainty and incomplete information often rely on their feelings when they make decisions (Schwarz, 1990).…”
Section: Big Five Theory and Perceived Justicementioning
confidence: 99%
“…The underlying logic of these beneficial effects is that this group of people are more motivated, experience more positive affect and have greater interpersonal and leadership skills (Dietl and Kombeiz, 2020). Extraversion is also related to social interaction (Chen et al, 2020). Using smartphone sensing, Harari et al (2019) found that extraversion was positively correlated to the frequency of outgoing phone calls, text messages, use of messaging applications and social media.…”
Section: Big Five Theory and Perceived Justicementioning
confidence: 99%